Study of Children's Literature "Magic Watermelon Seeds" in the Implementation of Didactic Bibliotherapy-Based Character Education - Desty Putri Hanifah; Rochyani Lestiyanawati (Jurnal Elementaria Edukasia, 2023)
Children's literature is used as a medium forChildren's literature is a medium for the formation of children's character. Therefore, children's literature should be reviewed so that children's moral values can be optimally taught. The purpose of this research is to study and review children's literature before it is given to children or students at school. The approach to studying children's literature uses a didactic bibliotherapy model or therapy using book media. The study is based on library research. The book studied is a children's book entitled "The Magic Watermelon Seeds", which was published by the Ministry of Education and Culture in cooperation with Room to Read. The results of the research show that the book contains seven implicit moral values. The seven moral values are: 1) emulating good character; 2) being careful in doing; 3) gracefully accepting fate; 4) generous, sincere, and compassionate to everyone; 5) rewarding people who do something expecting conditions; 6) generous to brothers; and 7) living harmoniously and side by side. The content of these moral values can be transmitted to children through a didactic bibliotherapy approach using the method of reading aloud individually or in groups.